Penerapan Laporan Keuangan Standar Akuntansi Keuangan Entitas Mikro Kecil dan Menengah (SAK-EMKM) Pada CV. Riau Jaya Group - Hafizh Dzaky Hawari; Emi Vita Liani; Rizki Aryanto; Windy Nurramadani; Sri Cahyani; Siti Rodiah (International Forum of Researchers and Lecturers, 2024)
The purpose of this research is to analyze the application of the SAK EMKM Micro Entity Accounting Standards at the CV. Riau Jaya Group service bureau service company. This is due to companies’ concerns about data and a lack of knowledge about the importance of financial reports using SAK EMKM. The analysis in this research uses a qualitative descriptive method to determine the obstacles or problems faced by service bureau companies in implementing financial reports by SAK EMKM. Data collection techniques in this research were used using field research and documentation. The results of this research show that the CV of the service bureau company. Riau Jaya Group still uses financial reports manually.